Performance of the North Morowali Regency General Election Commission in the 2020 Regional Head and Deputy Regional Head Elections - Awaludin, Ahlan; Hasbullah, Hasbullah; Nur Alamsyah, Moh. (Lafadz Jaya Publisher, 2024)
This research aims to analyze the performance of the North Morowali Regency General Election Commission in the 2020 Regional Head and Deputy Regional Head Elections, to what extent the Morowali General Election Commission carries out its duties and authority to ensure that the stages of holding the 2020 North Morowali Regency regional head election run effectively. and efficiently, resolving complaints by providing satisfaction in service, responding to the needs of all interested parties, as well as implementing correct administrative principles and how elections are carried out with full responsibility. This research uses a qualitative approach as a choice that guides research in conducting exploration, looking closely at a social situation to achieve a broad understanding and comprehensive analysis, producing or describing data in the form of narrative words about objects in the form of behavior observed when the search is carried out, The performance of the Morowali KPU was observed using the four aspects put forwardAgus Dwiyanto namely Productivity, Service Quality, Responsiveness, Responsibility and Accountability. The research results show thatThe election stage is divided into two stages, namely preparation and implementation, in the discussion of implementation it is specified, namely starting from candidate registration, determining candidate pairs, campaigning, voting and counting votes, and determining selected candidate pairs and resolving violations and result disputes. The performance of the North Morowali Regency General Election Commission in holding the 2020 regional head and deputy regional head elections has been carried out well in accordance with applicable laws and regulations. Every activity and decision rule that is issued is based on KPU regulations. However, in the realization of the implementation of each stage of the regional elections, there is a possibility that the activities and decisions taken are not included in the KPU regulations, so a joint decision with the election participants is needed to make a decision which as long as it does not conflict with existing regulations. Several things that need to be corrected regarding improving service quality are the availability of adequate facilities, office facilities that are not optimal, especially office buildings that are old. This is the most basic thing that needs to be improved and there will even be a new office building built. Because a good building covers many aspects of maximum service. In terms of human resources, the service process has also been maximized which fulfills a sense of satisfaction. Because every data needed by the public and election participants can be fulfilled quickly and precisely.